4-Octyl itaconate inhibits synovitis in the mouse model of post-traumatic osteoarthritis and alleviates pain - Yu-Zhen Tang; Wan Chen; Bao-Yun Xu; Gang He; Xiu-Cheng Fan; Kang-Lai Tang (Chinese Journal of Traumatology)
Purpose: To investigate the pathological changes of the synovium in mice with post-traumatic osteoarthritis (PTOA) treated with 4-octyl itaconate (4-OI) and evaluate the therapeutic effects of 4-OI. Methods: In the phenotypic validation experiment, the mice were randomly divided into 3 groups: wild-type (WT) group, sham group, and destabilization of the medial meniscus (DMM) group. Through MRI, micro-CT, and histological analysis, it was determined that the DMM surgery induced a mouse PTOA model with significant signs of synovitis. At 12 weeks post-DMM surgery, synovial tissues from the DMM group and WT group mice were collected for ribonucleic acid sequencing analysis. In the 4-OI treatment experiment, mice were randomly divided into the sham group, DMM group, DMM + 4-OI (50 mg/kg) group, and DMM + 4-OI (100 mg/kg) group. Von Frey tests and open field tests were conducted at intervals during the 12 weeks following the DMM surgery. After 12 weeks of surgery, the efficacy of 4-OI treatment on PTOA in mice was evaluated using MRI, micro-CT, histological analysis, and quantitative real-time polymerase chain reaction. Finally, we utilized network pharmacology analysis to predict the mechanism of 4-OI in treating PTOA synovitis and conducted preliminary validation. Statistical analysis was performed using one-way ANOVA and the Kruskal-Wallis test. Difference was considered statistically significant at p < 0.05. Results: The DMM surgery effectively induced a PTOA mouse model, which displayed significant symptoms of synovitis. These symptoms included a notable increase in both the number of calcified tissues and osteophytes (p < 0.001), an enlargement of the calcified meniscus and synovial tissue volume (p < 0.001), and thickening of the synovial lining layer attributable to M1 macrophage accumulation (p = 0.035). Additionally, we observed elevated histological scores for synovitis (p < 0.001). Treatment with 4-OI inhibited the thickening of M1 macrophages in the synovial lining layer of PTOA mice (p < 0.001) and reduced fibrosis in the synovial stroma (p = 0.004). Furthermore, it reduced the histological scores of knee synovitis in PTOA mice (p = 0.006) and improved the inflammatory microenvironment associated with synovitis. Consequently, this treatment alleviated pain in PTOA mice (p < 0.001) and reduced spontaneous activity (p = 0.003). Bioinformatics and network pharmacology analyses indicated that 4-OI may exert its therapeutic effects by inhibiting the differentiation of synovial Th17 cells. Specifically, compared to the lipopolysaccharide stimulation group, 4-OI reduced the levels of positive regulatory factors of Th17 cell differentiation (IL-1: p < 0.001, IL-6: p < 0.001), key effector molecules (IL-17A: p < 0.001, IL-17F: p = 0.004), and downstream effector molecules in the IL-17 signaling pathway (CCL2: p < 0.001, MMP13: p < 0.001). Conclusion: 4-OI is effective in inhibiting synovitis in PTOA, thereby alleviating the associated painful symptoms.